Effects of bilateral uterine ligation on skeletal growth in rats - Oyhenart, Evelia Edith (2002)
The aim of the present study was to assess the catch-up growth in the postcranial skeleton of intrauterine growth retarded (IUGR) rats. Male and female Wistar rats were assigned to one of the following groups: controls, sham-operated, IUGR. The IUGR was produced by uterine vessels bending (day 14th of pregnancy). Trunk, pelvis, femur and humerus were measured on Rx of each animal, from I to 84 days of age. Data were processed by repeated analysis of variance and LSD post hoc test. The reduced placental blood flow disturbed the skeletal growth in pups, with the axial skeleton relatively more affected than the bones of the extremities. The catch up only took place in femur length of both sexes. The widths of long bones remained significantly retarded. We concluded that nutritional rehabilitation during the postnatal period might not be enough to allow a complete growth recovery.